None left behind : the 10th Mountain Division and the triangle of death - Sasser, Charles W. (St. Martin's Press, 2009)
The War on Terror has drawn the Army's 10th Mountain Division to the most dangerous parts of Iraq. This book documents that danger, specifically the events of May 12, 2007, when Iraqi insurgents killed four soldiers and an Iraqi translator and, presumably, seized three others.